The relations between perceived stress, communication skills and psychological symptoms in oncology nurses - ÜNSAL, GÜL (AVES PRESS LTD, 2015)
Objective: This study aims to determine the correlation between perceived stress, communication skills and psychological symptoms in oncology nurses. Methods: The study was conducted in collaboration with 102 nurses working in oncology departments of hospitals in Istanbul. The data was collected through Questionnaire Form, Perceived Stress Scale (PSS), Communication Skills Assessment Scale (CSAS) and Brief Symptom Inventory (BSS). Descriptive statistical analysis and spearman correlation analysis were used to evaluate the data. Results: Nurses received 16.85 (SD=6.08) points from PSS, 73.34 (SD=23.28) points from CSAS, and lastly 32.68 (SD=33.13) points from BSI. 84.3% of the nurses reported experiencing communication problems with angry and agitated patients. There was a negative correlation between PSS and CSAS (r=-0.28; p<0.01). A positive correlation was found between PSS and BSI total scores (r=0.50; p<0.01) and all the other sub-dimensions. Conclusion: Improving communication skills of oncology nurses and the interventions for their perceived stress levels may have effects as promoting their own psychological health as well as decreasing communicational difficulties with the patients and their families; and thus, it may affect the quality of care.
Keywords: oncology nurse; communication; perceived stress; psychological symptoms